Identifying Research Priorities in Musculoskeletal Trauma Care in Sub-Saharan Africa. Issue 1 (28th January 2022) - ,
Abstract : Background: In low and middle-income countries (LMICs), individuals suffer from a disproportionately higher number of musculoskeletal (MSK) injuries compared with those living in a high-income setting. However, despite the higher burden of death and disability from MSK injuries in LMICs, there has been little policy, research, and funding invested in addressing this distinctly overlooked problem. Using a consensus-based approach, the aim of this study was to identify research priorities for clinical trials and research in MSK trauma care across sub-Saharan Africa. Methods: A modified Delphi technique was utilized; it involved an initial scoping survey, a 2-round Delphi process, and, finally, review by an expert panel with members of the Orthopaedic Research Collaboration in Africa. This study was conducted among MSK health-care practitioners treating trauma in sub-Saharan Africa. Results: Participants from 34 countries across sub-Saharan Africa contributed to the 2 rounds of the Delphi process, and priorities were scored from 1 (low priority) to 5 (high priority). Public health topics related to trauma care ranked higher than those focused on clinical effectiveness, with the top 10 public health research questions scoring higher than the top 10 questions for clinical effectiveness. Ten public health and 10 clinical effectiveness questions related to MSK trauma care were identified; the highest-ranked questions in the respective categories were related to education and training and to the management of femoral fractures. Conclusions: This consensus-driven research priority study will guide health-care professionals, academics, researchers, and funders to improve the evidence on MSK trauma care across sub-Saharan Africa and inform funders about priority areas of future research.